Implementation of the Use of the Guide Note Learning Method Taking in Mathematics - Yenni Arnas; Ika Endrawijaya; Nurudin Siraj (EduLine: Journal of Education and Learning Innovation, 2022)
The process of learning mathematics in the classroom is strongly influenced by the role of teachers and students as individuals who are directly involved in the learning process. As an intermediary, the teacher must know where the sources of information for certain knowledge are and regulate the mechanism for obtaining it if students need it at any time. Teachers often have difficulty in carrying out mathematics learning, especially in the material of building space. Students find it difficult to understand concepts in spatial structure, so they seem confused in solving problems related to spatial structure, for example in the form of story questions. In addition, teachers are often confused in determining learning methods so that students can understand the material presented. This study aims to determine the differences in learning outcomes of mathematics using the Guide Note Taking method. This research was conducted in the Even Semester. The variables in this study consist of one independent variable and one dependent variable. The mathematics learning outcomes of students who were taught using the Guide Note Taking method were considered good. The mathematics learning outcomes of students who were taught using the guide note taking method were good and satisfying.